PENGEMBANGAN DAYA TARIK OBJEK WISATA TELUK JERING KECAMATAN TAMBANG KABUPATEN KAMPAR - Salambue, Roni; Fatayat, Fatayat; Mahdiyah, Evfi; Andriyani, Yanti (Jurnal Pengabdian Masyarakat Multidisiplin, 2020)
One tour that can support the regional economy found in Kampar Regency is Teluk Jering which is located in Dusun III in Teluk Kenidai Village, Tambang District, Kampar Regency. The location is also called Pantai Cinta because the sand on the edge of the river has white sand and clean beach. Many residents who came from Pekanbaru and other areas deliberately visited Teluk Jering. The development is carried out by making road directions to the location of attractions, gates, photo spots, information signs, the website of the Teluk Jering village and promotion and publication on social media. The development and tourism of Teluk Jering will have an impact on the arrival of visitors to the Teluk Jering tourist attraction will increase the income of the people of Teluk Jering Village. The tourism sector is a potential sector to be developed as a source of regional income. The development of tourism depends on the visits that come to visit the place. The increase in the number of visits that occur is a reflection of the continued development of tourism, to maintain and increase the number of tourist visits